A simple method for residual stress measurements in thin films by means of focused ion beam milling and digital image correlation - Krottenthaler, Markus; Schmid, Christoph; Schaufler, Jens; Durst, Karsten; Göken, Mathias (Surface & Coatings Technology, 2013)
Hydrogenated amorphous carbon (a-C:H) coatings contain substantial residual stresses which particularly influence the failure behaviour of the coating system. However, measuring their residual stresses with conventional methods is not trivial. In this work, a simple method is presented to determine residual stresses of thin films locally by using stress relaxation tests by means of focused ion beam (FIB) milling and digital image correlation (DIC). It is shown, that the H-bar geometry, as it is used for TEM lamella preparation, is especially suitable for such measurements. Displacements due to relaxation of residual stresses are tracked using DIC and the stresses are obtained by correlation with finite element analysis. The method is applied to determine residual stresses of two a-C:H coatings processed with different deposition processes and parameters. It was found, that the coatings differ in their mechanical properties as well as in their residual stress state. The proposed method offers therefore a simple way for analysing residual stresses in thin amorphous coatings.
WW1::951